2016
DOI: 10.2967/jnumed.115.171066
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Minimum 124I Activity Required in Uptake Measurements Before Radioiodine Therapy for Benign Thyroid Diseases

Abstract: This study aimed to assess a hypothetical minimum administered activity of 124 I required to achieve comparability between pretherapeutic radioiodine uptake (RAIU) measurements by 124 I PET/CT and by 131 I RAIU probe, the clinical standard. In addition, the impact of different reconstruction algorithms on 124 I RAIU and the evaluation of pixel noise as a parameter for image quality were investigated. Methods: Different scan durations were simulated by different reconstruction intervals of 600-s list-mode PET d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The radiometric distribution of cold nodules decreases significantly, and radiometric defects often appear. The difference between cold and cool nodules is the degree of reduction in iodine uptake at the nodular site (21). Several studies have suggested that radionuclide scanning (ECT) can help clinicians understand the functional status of the thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…The radiometric distribution of cold nodules decreases significantly, and radiometric defects often appear. The difference between cold and cool nodules is the degree of reduction in iodine uptake at the nodular site (21). Several studies have suggested that radionuclide scanning (ECT) can help clinicians understand the functional status of the thyroid.…”
Section: Discussionmentioning
confidence: 99%